Guilty by reason of insanity : why the Democrats must not win - Limbaugh, David (Regnery Publishing, a division of Salem Media Group, 2019)
The left has truly lost its mind. The party out of power used to be “the loyal opposition.” No longer. Now it<U+2019>s “the Resistance.” The left, abandoning any pretense of fairness and decency, has declared political war on President Trump. Waged by a stunningly broad array of militants<U+2014>the Democratic Party, countless left-wing interest groups, radical academics, the liberal mainstream media, Antifa shock troops, Hollywood, and the tech oligarchs<U+2014>this political war is aimed not only at conservative ideas but also at Trump supporters, even teenagers wearing MAGA hats.